Lost in Translation: Examining Translation Errors in Arabic-English Translated Abstracts Published in Gharyan University Journal (مجلة جامعة سرت للعلوم الانسانية, 2023)
Abstracts of research articles should be translated from Arabic into English before being submitted for publication in Libyan academic journals. Because English publishing allows non-native speakers to gain international recognition (Duszak & Lewkowicz, 2008). This study aimed to identify the most typical errors made while translating the Arabic abstracts into English. For this purpose, a corpus of 33 translated abstracts of research articles (RA) were analyzed.  They were extracted from 11 issues of the Journal of Gharyan University and were published from 2016 to 2021. The analytical frameworks developed by Popescu (2013) and Laio (2010) were adopted. A preliminary analysis was carried out to develop a new category of translation errors that is appropriate for the current corpus. The results revealed a large number of errors in the translated abstracts. They were translation, stylistic, and linguistic errors. It is suggested that the Journal of Gharyan University should devote more effort to evaluating and polishing the translated abstracts before publishing the articles. If they wish to obtain a worldwide reputation, they should also include translators on the journal's editorial board to translate the Arabic abstracts into English appropriately.
Keywords: Abstracts; Translation Errors; Gharyan University Journal; English